COMPARATIVE ANALYSIS METHOD OF SOFT SOIL IMPROVEMENT PREFABRICATED VERTICAL DRAIN WITH SAND COMPACTION PILE, CASE STUDY OF LAND PREPARATION COAL TERMINAL PORT SITE, LUBUK TUTUNG KALIMANTAN - Nosa A, Anggoro
In a construction site, there are often found soil condition that are not in accordance with the existing design criteria, so it need some improvement for get a better soil condition. On the land preparation at coal terminal project of the ports on the Lubuk Tutung area, East Kalimantan, there are founded that the bearing capacity of the soil is 44 kN/m2 and settlement of soil is 0.84 m by the time it takes as many as 322 Years, and it is not suitable according to design criteria. By it condition, the soil was proposed to get two soil improvement method, which is prefabricated vertical drains and sand compaction pile, where both methods will be compared in this research. The first soil improvement method, prefabricated vertical drains method, is accelerated the time to reach the final stage of settlement with the gradual accumulation with the time it takes for 10 months, but this method cannot reduce the size of the soil settlement. The second method, the sand compaction pile method, can reduce the size of the settlement that occurred at 0.41 m in 13 months, so the use of the sand compaction pile method is more effective than the use of prefabricated vertical drain soil improvement method for improving the soil condition.